2014
DOI: 10.3402/gha.v7.23568
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening health systems by health sector reforms

Abstract: BackgroundThe rising burden of disease and weak health systems are being compounded by the persistent economic downturn, re-emerging diseases, and violent conflicts. There is a growing recognition that the global health agenda needs to shift from an emphasis on disease-specific approaches to strengthening of health systems, including dealing with social, environmental, and economic determinants through multisectoral responses.MethodsA review and analysis of data on strengthening health sector reform and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 31 publications
(52 reference statements)
1
79
0
Order By: Relevance
“…Effective leadership has been identified as key to promoting health care reform in low income countries (Senkubuge, Modisenyane, & Bishaw, 2014). A recent systematic review of transformational leadership training for physicians revealed few interprofessional and transprofessional training programs in the United States and no such programs in Africa (Straus, Soobiah, & Levinson, 2013).…”
Section: Afya Bora Narrows Gaps In Leadership Trainingmentioning
confidence: 99%
“…Effective leadership has been identified as key to promoting health care reform in low income countries (Senkubuge, Modisenyane, & Bishaw, 2014). A recent systematic review of transformational leadership training for physicians revealed few interprofessional and transprofessional training programs in the United States and no such programs in Africa (Straus, Soobiah, & Levinson, 2013).…”
Section: Afya Bora Narrows Gaps In Leadership Trainingmentioning
confidence: 99%
“…Senkubuge and colleagues (3) argue that there is no single global or regional policy formula for health sector reform and that it will depend on a country’s history, values, and culture. On the one hand, many developed countries are approaching health reform from a cost-efficiency perspective, aiming to reduce costs while maintaining quality of care and improvements in longevity.…”
Section: The Impetus For Health Sector Reformmentioning
confidence: 99%
“…There is growing evidence that the global health agenda needs to shift from an emphasis on disease-specific approaches of interventions to strengthening of health systems, including dealing with social, environmental and economic determinants through multi-sectorial responses (Lancet, 2004;Senkubuge et al, 2014). The World health Organizations (WHO) defines health systems as all organizations, people and actions whose primary intent is to promote, restore and maintain health (WHO, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The health systems framework consists of six building blocks, namely; service delivery, health work force, health information systems, medical products including vaccines and other technologies, health financing, leadership and governance (WHO, 2007). These building blocks interact with other facets to constitute a system (Senkubuge et al, 2014). Improvement of healthcare service delivery requires synergies in the functionality of the building blocks at all levels of implementation including the district (Sengkubuge et al, 2014).…”
Section: Introductionmentioning
confidence: 99%